The Influence of Form-Focused Instruction on the L2 Chinese Oral Production of Korean Native Speakers - Chen, Mo; Li, Wenya (Frontiers in Psychology, 2022)
Form-focused instruction (FFI) can help second language (L2) learners notice the forms of language, which is conducive to the acquisition of linguistic forms. Two types of FFIs had been proposed, including focus-on-formS (FonFs) and focus-on-form (FonF). Previously, studies on FFI in L2 classroom teaching have focused mainly on the influence of two types of FFIs on the L2 acquisition of grammar and vocabulary. The influence of FonFs and FonF on L2 oral production, however, has been addressed less often. The advantages and disadvantages of different teaching methods in FonFs and FonF have not been well investigated. On the basis of Schmidt’s noticing hypothesis (1990), VanPatten’s input processing hypothesis (2007), and Long’s interactive hypothesis (1996), we investigated the effects of teaching goals, teaching steps, and interactive activities in FonFs and FonF on the complexity, accuracy, and fluency of 32 native Korean speakers’ L2 Chinese oral production. We found that FFI significantly improved the performance of L2 Chinese oral production, although different FFIs had different effects on complexity, accuracy, and fluency. FonF and FonFs could improve both complexity and accuracy, whereas FonF also significantly improved fluency, which was not observed in FonFs. Furthermore, we found that the level of L2 proficiency could modulate the interaction between instruction methods and learning outcomes. For low-proficiency learners, FonF was more helpful for the improvement of fluency. For high-proficiency learners, FonFs was more helpful for the improvement of accuracy. These results demonstrated that teachers should pay attention to the interaction between specific teaching conditions with different L2 proficiency and learning outcomes when implementing FFI. The findings of this study have important implications for the design of procedures and interactive activities of L2 spoken Chinese teaching.